PERAN UNITED NATION CHILDREN’S FUND DALAM MENGATASI PERDAGANGAN ANAK DI PANTAI GADING TAHUN 2011-2016 - Yori Geovani Regina; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to explain how the condition of child trafficking problems in Ivory Coast as well as explain how the role of UNICEF in addressing the issue of child trafficking in Ivory Coast in 2011-2016.The author uses the pluralism perspective, which is supported by the theory of international organizations and the concept of role and level of group analysis, as the actor. The concept leads to qualitative methods and literature studies as a source of information.The results of this study describe the problem solving problem of child trafficking in Ivory Coast, UNCEF in collaboration with the Ivory Coast government, establishing a program of child trafficking, the National Plan of Action for the Elimination of Child Trafficking, Increasing the victim economy, and Creating a program and initiative at outside the ivory Coast state to help integrate, reintegrate and recover child victims.Keywords: Role, UNICEF, Child Trafficking, Pluralism